2022
DOI: 10.7189/jogh.12.03027
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the global health potential of dried blood spot cards

Abstract: The use of dried blood spot cards offers a unique opportunity to further develop international newborn screening or other diagnostic or population level screening initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Various other studies relating to the use NBS laboratory data and/or DBSs have been reported: the use of archived DBSs to retrospectively provide valuable etiological information on the complex interplay between environmental exposures, biological response, and population phenotypes [ 159 ]; the underutilization of archived NBS specimens in health disparity research [ 160 ]; the influence of ethnicity on false-positive metabolic marker levels for four screened conditions [GA-I, methylmalonic acidemia, ornithine transcarbamylase deficiency (OTCD), and VLCAD] in a diverse newborn population [ 161 ]; and systematic examination of NBS data to determine whether timing of specimen collection (<24 h of age, 24–48 h of age, >48 h of age) could impact the performance of NBS for selected metabolic disorders on the RUSP [carnitine transport defect (CTD), IVA, MMA, and PKU] [ 162 ]. A number of recent reports have described continuing studies involving USA and Canadian partners with other collaborators, to predict gestational age using NBS DBS specimens to help inform medical care for newborns in low-resource settings: a 2021 report outlining a research project in which specimens from sub-Saharan Africa and Asia would be analyzed in Canada [ 163 ]; a report defining a project to validate a gestational age estimation algorithm using DBSs spot in low-resource settings in Zambia, Kenya, Bangladesh, and Zimbabwe [ 164 ]; a 2022 description of the feasibility specimen collection, shipping, and analysis for DBSs collected in Bangladesh, Kenya, and Zambia, and tested in Ontario, Canada for NBS, and possibly other activities [ 165 ]; and a 2023 report of three gestational age estimation models using ELASTIC NET multivariable linear regressions on cohorts in Canada and their application in Zambia and Bangladesh (data from heel sticks were superior to cord blood data) [ 166 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various other studies relating to the use NBS laboratory data and/or DBSs have been reported: the use of archived DBSs to retrospectively provide valuable etiological information on the complex interplay between environmental exposures, biological response, and population phenotypes [ 159 ]; the underutilization of archived NBS specimens in health disparity research [ 160 ]; the influence of ethnicity on false-positive metabolic marker levels for four screened conditions [GA-I, methylmalonic acidemia, ornithine transcarbamylase deficiency (OTCD), and VLCAD] in a diverse newborn population [ 161 ]; and systematic examination of NBS data to determine whether timing of specimen collection (<24 h of age, 24–48 h of age, >48 h of age) could impact the performance of NBS for selected metabolic disorders on the RUSP [carnitine transport defect (CTD), IVA, MMA, and PKU] [ 162 ]. A number of recent reports have described continuing studies involving USA and Canadian partners with other collaborators, to predict gestational age using NBS DBS specimens to help inform medical care for newborns in low-resource settings: a 2021 report outlining a research project in which specimens from sub-Saharan Africa and Asia would be analyzed in Canada [ 163 ]; a report defining a project to validate a gestational age estimation algorithm using DBSs spot in low-resource settings in Zambia, Kenya, Bangladesh, and Zimbabwe [ 164 ]; a 2022 description of the feasibility specimen collection, shipping, and analysis for DBSs collected in Bangladesh, Kenya, and Zambia, and tested in Ontario, Canada for NBS, and possibly other activities [ 165 ]; and a 2023 report of three gestational age estimation models using ELASTIC NET multivariable linear regressions on cohorts in Canada and their application in Zambia and Bangladesh (data from heel sticks were superior to cord blood data) [ 166 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other NBS studies on Bangladeshi newborns have been reported with particular emphasis on local incidences of metabolic and other conditions detectable by NBS: a study of LC-MS/MS techniques, establishing cutoff values for various amino acids and acylcarnitines, to assist government authorities in installing and establishing NBS [ 435 ]; a Canadian collaboration study of CH and HGB in Matlab, Bangladesh to determine incidences and to validate the use of an offsite remote laboratory [ 436 ]; a report on the ease of use of DBSs for remote laboratory testing as part of NBS in LMICs [ 165 ]; a study to assess the prevalence of α-thalassemia and provide a model for NBS [ 437 ]; and a study to demonstrate the feasibility of NBS for SCD and β-thalassemia [ 438 ]. Since NBS for conditions like SCD, thalassemias and other genetic conditions is aided by population education and family counseling when cases are detected, it is important to consider the availability of trained genetic counselors.…”
Section: Resultsmentioning
confidence: 99%
“…[9] This elevated transferrin fraction after abnormal glycosylation was named carbohydrate-deficient transferrin (CDT) [10][11][12][13] and is used as a biomarker to identify persistent heavy drinking and to monitor abstinence during treatment. [15], [16] Compared with the use of conventional human serum samples, the use of Dried blood spots (DBS) samples from blood cards for CDT screening has many advantages [14], [15] , including a simple and minimally invasive sampling procedure, easy storage of the samples, minimal transportation requirements, and reduced risk of infection with some of the most risky blood-borne infections (HIV, hepatitis, etc.) [16] .…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms were originally developed and internally validated in a large cohort of newborns in Ontario, Canada [14,15]. Refinements to the algorithms incorporated machine learning and improved the accuracy of gestational age estimations [12,16]. Here we evaluate the use of these algorithms in a population of infants born in Siaya County, Kenya.…”
Section: Introductionmentioning
confidence: 99%